Transparent Conducting Films - Pal, Kaushik (IntechOpen, 2019)
This book presents a significant class of materials that has recently drawn increasing interest in applications of active devices and as a critical component in any structure that requires both electrical connectivity and optical transparency. Despite their technological importance and relatively long history of utilization, our understanding of the existing set of transparent conduction oxide (TCO) material is only now receiving the kind of combined fundamental/experimental material research attention that will inevitably lead to new material discoveries and novel applications. Overall, it is clear that transparent conducting films and transparent conductors are a vibrant field that is advancing rapidly across an ever-broadening spectrum of applications. We hope this book will provide a valuable reference for those interested in the topic and stimulate additional development of new TCO materials and their applications.